(untitled) ("Journal "U". Economy. Management. Finance.", 2022)
The article discusses the mechanisms of state regulation of the development of socially oriented non-profit organizations used in the Russian Federation, presents their characteristics. The author highlights the advantages of the existing system of state regulation of the development of socially oriented non-profit organizations: its integrity, coverage of all territorial levels at which non-profit organizations operate, promotion of the diversity of the development of the non-profit sector, creation of conditions for the development of competition in the social services market. The author suggests directions for improving state regulation of SONКO development.